Lateralized Deficits of Disgust Processing After Insula-Basal Ganglia Damage - Holtmann, Olga; Bruchmann, Maximilian; Mönig, Constanze; Schwindt, Wolfram; Melzer, Nico; Miltner, Wolfgang H. R.; Straube, Thomas (Frontiers in Psychology, 2020)
A growing body of evidence suggests a role of the insular cortex (IC) and the basal ganglia (BG) in the experience, expression and recognition of disgust. However, human lesion research, probing this structure-function link, has yielded rather disparate findings in single cases of unilateral and bilateral damage to these areas. Comparative group approaches are needed to elucidate whether disgust-related deficits specifically follow damage to the IC-BG system, or whether there might be a differential hemispheric contribution to disgust processing. We examined emotional processing by means of a comprehensive emotional test battery in four patients with left- and four patients with right-hemispheric lesions to the IC-BG system as well as in 19 healthy controls. While single tests did not provide clear-cut separations of patient groups, composite scores indicated selective group effects for disgust. Importantly, left-lesioned patients presented attenuated disgust composites, while right-lesioned patients showed increased disgust composites, as compared to each other and controls. These findings propose a left-hemispheric basis of disgust, potentially due to asymmetrical representations of autonomic information in the human forebrain. The present study provides the first behavioral evidence of hemispheric lateralization of a specific emotion in the human brain, and contributes to neurobiological models of disgust.